Child protection decision-making: social workers' perceptions. Issue 2 (3rd April 2018) - Nyathi, Nhlanganiso
ABSTRACT: Decision-making is located at the heart of social work as a core professional activity, because much of what social workers do concerns decisions about future courses of action. Drawing on elements of the learning together systems model and Falkov's Systemic Family Model, this study investigated social workers' perceptions regarding how child protection decisions are made. Evidence was drawn from a constructivist–-interpretivist qualitative research design, involving 16 semi-structured interviews with qualified and experienced social workers and 20 direct, non-participant observations of child protection meetings. Evidence from the study suggests that professionals and family members do not rely entirely on the guidance on the threshold criterion of the likelihood and significance of risk of harm when making decisions. Instead, they use discretionary intuition and analytical judgement, involving multidimensional criteria which includes consensus between professionals and with family members; individual professional's state of mind; other agencies and professionals' priorities as well as external factors such as the availability of resources. Conclusion can be drawn that existing guidance on decision-making is inadequate, hence the discretionary use of a combination of intuitive heuristics and analytical thinking in a complementary manner. This study, therefore, contributes to considerable conceptual clarity regarding the complex child protection decision-making process.